Justice for Victims: A Comparative Study of Sanctions for Sexual Violence under UU TPKS and Jarimah Ta’zir - Islamul Haq (IAIN Parepare, 2023)
The enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes (UU TPKS) marks a transformative momentum in Indonesia's victim-oriented criminal law. However, within a religious society, doubts often arise regarding the alignment of these regulations with Islamic values. This study aims to analytically compare the construction of sexual violence sanctions in the TPKS Law and Islamic Criminal Law (Jarimah Ta'zir) and the extent to which both provide justice for victims. The research method employed is normative legal research with statutory, conceptual, and comparative approaches. Primary, secondary, and tertiary legal materials were used as data sources, analyzed through descriptive qualitative content analysis. The results indicate a substantial convergence between the two legal systems, where the restitution mechanism in the TPKS Law shares functional similarities with the concept of Diyat Ta'zir, aimed at recovery (jawabir). Furthermore, the treatment and rehabilitation sanctions in the TPKS Law are found to be consistent with the principles of ta'dib and ishlah in Islamic law. Additionally, financial sanctions in the form of fines under UU TPKS correspond to the concept of ta'zir bi al-mal in Islamic jurisprudence, while supplementary sanctions such as publication of the perpetrator's identity reflect the Islamic concept of tashhir. The study concludes that the 2022 TPKS Law is a modern manifestation of the objectives of public interest (Maqashid al-Syari'ah), providing holistic protection for human dignity through both outward and inward dimensions recognized by Sharia. It is recommended that law enforcers optimize the application of UU TPKS sanctions without hesitation, as they substantively meet Islamic standards of justice, and that future empirical research be conducted to evaluate the actual effectiveness of sanction enforcement in the field.